A sodium ion battery composite diaphragm and a preparation method thereof, and a sodium ion battery

CN122739730APending Publication Date: 2026-09-11广东兆瑞新能源技术有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611151824.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-09-11

AI Technical Summary

Technical Problem

此类填料吸水时放热会析出可溶性杂质,容易破坏钠电界面膜、加剧容量衰减

Benefits of technology

本发明的复合隔膜,采用正负极侧差异化梯度功能设计,正极侧设置陶瓷涂层,提升隔膜穿刺强度与热稳定性,阻挡正极脱落碎屑、钠枝晶刺穿隔膜;负极侧设置除水抑枝晶涂层,以海藻酸钠和丙烯酸作为粘结载体,内部均匀分散4A分子筛,实现选择性长效吸附电芯内部游离水分,阻断钠盐水解生成HF副反应,同时粘结基体含有大量极性亲水基团,可均匀吸附电解液、分散钠离子通量,避免负极局部电流密度过高,从源头减少钠枝晶成核。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122739730A_ABST
    Figure CN122739730A_ABST
Patent Text Reader

Abstract

This invention relates to the field of sodium-ion battery separator materials, specifically to a sodium-ion battery composite separator and its preparation method, and a sodium-ion battery. The sodium-ion battery composite separator of this invention has a three-layer composite structure, comprising a ceramic coating, a porous polyolefin base membrane, and a water-removing and dendrite-inhibiting coating. The ceramic coating is disposed on the side of the porous polyolefin base membrane used for bonding to the positive electrode of the sodium-ion battery; the water-removing and dendrite-inhibiting coating is disposed on the side of the porous polyolefin base membrane used for bonding to the negative electrode of the sodium-ion battery; the thickness of the ceramic coating is greater than the thickness of the water-removing and dendrite-inhibiting coating. This invention, through its three-layer structure design of the ceramic coating, porous polyolefin base membrane, and water-removing and dendrite-inhibiting coating, achieves a comprehensive improvement in separator puncture strength, electrolyte wettability, moisture control, and battery cycle stability, making it suitable for the preparation and application of sodium-ion battery separators in large-scale energy storage power stations, low-speed vehicles, backup power supplies, and other similar scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery separator material technology, specifically to a sodium-ion battery composite separator and its preparation method, and a sodium-ion battery. Background Technology

[0002] Sodium-ion batteries have broad application prospects in large-scale energy storage due to the abundance and low cost of sodium resources. However, sodium-ion batteries face two unique technical challenges in practical applications: First, sodium salt electrolytes (such as NaPF6) are extremely sensitive to moisture. Even a trace amount of moisture inside the cell can trigger the hydrolysis of sodium salts to generate corrosive HF, which corrodes the positive electrode active material and the negative electrode SEI film, leading to battery capacity decay and gas bulging. Second, sodium ions have a large radius and tend to be unevenly distributed when deposited on the negative electrode surface, forming sodium dendrites. Dendrite growth can pierce the separator, causing short circuits or even thermal runaway.

[0003] As a key component of sodium-ion batteries, the separator's performance directly affects the battery's safety and cycle life. Currently, sodium-ion battery separators are mainly classified into the following categories: 1) Ceramic separators. This type of separator only coats a ceramic layer on the polyolefin base membrane side, relying on the ceramic layer to improve puncture strength and thermal stability. However, this separator lacks in-situ water removal capability and cannot eliminate the corrosion of the electrodes by HF generated from the hydrolysis of sodium salt electrolyte; moreover, it can only passively block dendrites and cannot improve the problem of uneven sodium ion distribution, and sodium dendrites are still prone to puncturing the separator under long-term cycling. 2) Molecular sieve water-absorbing separators. This type of separator introduces molecular sieves into the separator coating for water adsorption, but it does not have a gradient layered structure adapted to the positive and negative electrodes of sodium batteries. After the molecular sieves are mixed, they are prone to clogging the separator pores and increasing impedance; moreover, it only has a single function of water absorption and has not been modified to address the sodium dendrite problem; at the same time, ordinary molecular sieves are also prone to adsorbing carbonate electrolyte, causing capacity loss. 3) Water-absorbing filler separators such as calcium oxide and calcium chloride. When this type of filler absorbs water, it releases heat and precipitates soluble impurities, which can easily damage the sodium electrode interface film and exacerbate capacity decay.

[0004] Therefore, existing sodium-ion battery separators have limited functionality and lack a suitable integrated positive and negative gradient separator structure that can simultaneously achieve selective and long-lasting water removal, uniform control of sodium ion deposition, and high-temperature resistance and puncture prevention. Summary of the Invention

[0005] To overcome the shortcomings of existing technologies, the purpose of this invention is to provide a composite separator for sodium-ion batteries, its preparation method, and a sodium-ion battery. The composite separator provided by this invention has a three-layer structure: a ceramic coating, a porous polyolefin-based membrane, and a water-removing and dendrite-inhibiting coating. The ceramic coating provides thermal stability and mechanical support, while the water-removing coating enables precise moisture adsorption. Together, they achieve a comprehensive improvement in puncture strength, electrolyte wettability, moisture control, and cycle stability, making it suitable for energy storage sodium-ion batteries. This invention simultaneously solves technical problems such as the easy hydrolysis and gas generation of sodium salt electrolytes, continuous corrosion of electrodes by trace amounts of moisture, and easy puncture of the separator by sodium dendrites.

[0006] To achieve the above-mentioned technical objectives, in a first aspect, the present invention provides a sodium-ion battery composite separator, wherein the sodium-ion battery composite separator has a three-layer composite structure, comprising, in sequence, a ceramic coating, a porous polyolefin base membrane, and a water-removing and dendrite-inhibiting coating; wherein the ceramic coating is disposed on the side of the porous polyolefin base membrane used for bonding the positive electrode sheet of the sodium-ion battery; the water-removing and dendrite-inhibiting coating is disposed on the side of the porous polyolefin base membrane used for bonding the negative electrode sheet of the sodium-ion battery; the thickness of the ceramic coating is greater than the thickness of the water-removing and dendrite-inhibiting coating; and the raw materials for preparing the water-removing and dendrite-inhibiting coating, by mass parts, include: 8-15 parts of 4A molecular sieve, 3-5 parts of sodium alginate, 0.5-2 parts of acrylic acid, and 80-88 parts of conductive carbon black.

[0007] The porous polyolefin-based membrane serves as the membrane substrate, providing basic ion transport channels and overall flexible support. More preferably, the porous polyolefin-based membrane has a thickness of 12-16 μm and a porosity of 40%-48%; the material of the porous polyolefin-based membrane is polypropylene or polyethylene.

[0008] To enhance the differentiated functional design and application effect of the diaphragm, it is further preferred that the thickness of the ceramic coating is 1~2μm; the ceramic coating is a nano-alumina coating, and the average particle size of the nano-alumina is 200~400nm.

[0009] More preferably, the thickness of the water-removing and dendrite-inhibiting coating is 0.4~0.8μm.

[0010] More preferably, the 4A molecular sieve has a particle size of 100~300nm and a pore size of 0.3~0.5nm.

[0011] More preferably, the raw materials for preparing the water-removing and dendrite-inhibiting coating also include 80-120 parts of water.

[0012] A second aspect of the present invention provides a method for preparing the sodium-ion battery composite separator as described above, comprising the following steps: S1. After mixing nano-alumina, polyvinylidene fluoride, and N-methylpyrrolidone, the mixture is milled and filtered to obtain a ceramic slurry. The ceramic slurry is coated on one side of a porous polyolefin-based membrane, and then dried and cooled to obtain a single-sided ceramic membrane. S2. Sodium alginate, conductive carbon black, 4A molecular sieve, and acrylic acid are mixed in water to obtain a composite slurry. The non-ceramic side of the single-sided ceramic separator is used as the coating surface, and the composite slurry is coated on the coating surface. Then, it is dried and aged at room temperature to obtain the sodium-ion battery composite separator.

[0013] More preferably, the mass ratio of the nano-alumina, polyvinylidene fluoride, and N-methylpyrrolidone is (80~90):(5~15):(110~130); the drying temperature is 40~85℃; and the room temperature curing time is 15~30h.

[0014] A third aspect of the present invention provides a sodium-ion battery, comprising a positive electrode, a negative electrode, and a sodium-ion battery composite separator as described above; the positive electrode is bonded to the ceramic coating side of the sodium-ion battery composite separator, and the negative electrode is bonded to the water-removing and dendrite-inhibiting coating side.

[0015] More preferably, the positive electrode is a sodium iron pyrophosphate electrode; the negative electrode is a hard carbon electrode; the sodium iron pyrophosphate electrode is mainly prepared from sodium iron pyrophosphate, conductive carbon black, and polyvinylidene fluoride in a mass ratio of (90~94):(4~6):(2~4), and the dry film thickness of the positive electrode is 90~110μm; the hard carbon electrode is mainly prepared from hard carbon, conductive carbon black, and sodium alginate in a mass ratio of (88~92):(5~7):(3~5), and the dry film thickness of the negative electrode is 100~120μm.

[0016] The technical solution of the present invention has the following beneficial effects: The composite separator of this invention adopts a differentiated gradient functional design on the positive and negative electrode sides. A ceramic coating is set on the positive electrode side to improve the puncture strength and thermal stability of the separator, preventing positive electrode debris and sodium dendrites from piercing the separator. A water-removing and dendrite-inhibiting coating is set on the negative electrode side, using sodium alginate and acrylic acid as binders, with 4A molecular sieves uniformly dispersed inside to selectively and effectively adsorb free water inside the battery cell, blocking the side reaction of sodium salt hydrolysis to generate HF. At the same time, the binder matrix contains a large number of polar hydrophilic groups, which can uniformly adsorb electrolyte and disperse sodium ion flux, avoiding excessively high local current density at the negative electrode and reducing sodium dendrite nucleation from the source.

[0017] Therefore, this invention uses molecular sieves to eliminate local current unevenness caused by moisture, sodium alginate and acrylic acid to regulate the uniform deposition of sodium ions, and ceramic layer to provide physical protection. The three work synergistically, which can significantly reduce the safety hazards of micro short circuits and thermal runaway and improve battery cycle performance compared with existing single modified separators.

[0018] Furthermore, the composite separator preparation method of the present invention does not require large-scale modification of existing separator coating equipment, has low raw material costs, is compatible with various sodium-ion cells such as pouch, square, and cylindrical cells, and is suitable for large-scale mass production of existing separator coating production lines. It can be used to prepare sodium-ion battery separators for large-scale energy storage power stations, low-speed vehicles, backup power supplies, etc. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the structure of the sodium-ion battery composite separator in Embodiment 1 of the present invention; Explanation of reference numerals in the attached figures: 1-Ceramic coating; 2-Porous polypropylene base membrane; 3-Water-removing and dendrite-inhibiting coating. Detailed Implementation

[0020] To make the technical solutions and advantages of the present invention clearer, the present invention will be clearly and completely described below in conjunction with specific embodiments. Without departing from the scope or spirit of the present invention, those skilled in the art can make various improvements and changes to the specific embodiments of the present invention, which will be obvious to those skilled in the art.

[0021] This invention provides a sodium-ion battery composite separator, which has a three-layer composite structure, comprising a ceramic coating, a porous polyolefin base membrane, and a water-removing and dendrite-inhibiting coating. The ceramic coating is disposed on the side of the porous polyolefin base membrane used for bonding the positive electrode of the sodium-ion battery; the water-removing and dendrite-inhibiting coating is disposed on the side of the porous polyolefin base membrane used for bonding the negative electrode of the sodium-ion battery; the thickness of the ceramic coating is greater than the thickness of the water-removing and dendrite-inhibiting coating; the raw materials for preparing the water-removing and dendrite-inhibiting coating, by mass parts, include: 8-15 parts of 4A molecular sieve, 3-5 parts of sodium alginate, 0.5-2 parts of acrylic acid, and 80-88 parts of conductive carbon black.

[0022] Porous polyolefin-based membranes serve as the separator substrate, providing basic ion transport channels and overall flexible support. In one embodiment, the porous polyolefin-based membrane has a thickness of 12–16 μm and a porosity of 40%–48%; the material of the porous polyolefin-based membrane is polypropylene or polyethylene. When the membrane thickness is less than 12 μm, the overall puncture strength is insufficient, and it is easily punctured by sodium dendrites during long-cycle operation; a thickness greater than 16 μm increases the ion transport distance and raises the battery's internal resistance. A porosity less than 40% significantly reduces ion channels, resulting in noticeable rate decay; a porosity greater than 48% reduces the separator's mechanical strength and thermal stability, increasing the risk of thermal shrinkage.

[0023] To enhance the differentiated functional design and application effect of the separator, in one embodiment, the thickness of the ceramic coating is 1~2μm; the ceramic coating is a nano-alumina coating with an average particle size of 200~400nm. The ceramic coating mainly achieves high temperature resistance, improved puncture strength, prevention of positive electrode debris from piercing the separator, and suppression of positive electrode oxidation side reactions. Simultaneously, the thickness of the ceramic coating is greater than that of the water-removing and dendrite-inhibiting coating, forming a gradient structure of a dense positive electrode and a thin negative electrode.

[0024] The water-removing and dendrite-inhibiting coating of this invention comprises a 4A molecular sieve and a sodium alginate-bonded conductive substrate. The 4A molecular sieve can selectively adsorb free water inside the battery cell, blocking the hydrolysis side reaction of the sodium salt electrolyte. The sodium alginate-bonded conductive substrate can uniformly regulate the sodium ion deposition flux to inhibit sodium dendrite growth. In one embodiment, the thickness of the water-removing and dendrite-inhibiting coating is 0.4~0.8μm. When the coating thickness is less than 0.4μm, the molecular sieve loading is insufficient, the overall water absorption capacity is low, and it cannot effectively capture the trace amounts of water continuously generated during circulation; when the thickness is greater than 0.8μm, the organic binder and filler accumulate too thickly, blocking the membrane pores and increasing the battery's internal resistance.

[0025] In this invention, the raw materials for preparing the water-removing and dendrite-inhibiting coating include 4A molecular sieve, sodium alginate, acrylic acid, and conductive carbon black. If the proportion of molecular sieve is too low, the water absorption capacity per unit area is insufficient, making it difficult to continuously remove water from the battery cell after hydrolysis; if the proportion is too high, the matrix cannot completely coat the molecular sieve particles, and the filler may detach and clog the membrane pores during circulation. If the amounts of sodium alginate and acrylic acid are too low, the bonding force is insufficient, the molecular sieve is easily peeled off from the coating, and the number of polar groups is insufficient, making it impossible to uniformly disperse sodium ions; if the proportion is too high, there are too many organic components, the coating becomes dense, and the electrolyte wettability decreases. Furthermore, the conductive carbon black is uniformly dispersed inside the coating, eliminating local charge accumulation on the negative electrode, helping to reduce the probability of dendrite nucleation, and simultaneously improving the conductivity of the coating. Therefore, this invention controls the raw material amounts to 8-15 parts of 4A molecular sieve, 3-5 parts of sodium alginate, 0.5-2 parts of acrylic acid, and 80-88 parts of conductive carbon black.

[0026] By controlling the size of the 4A molecular sieve, it is possible to capture water without consuming electrolyte, thus achieving selective water removal. In one implementation, the particle size of the 4A molecular sieve is 100~300nm and the pore size is 0.3~0.5nm.

[0027] In one embodiment, the raw materials for preparing the water-inhibiting dendrite coating also include 80-120 parts of water.

[0028] The present invention provides a method for preparing the above-mentioned sodium-ion battery composite separator, comprising the following steps: S1. After mixing nano-alumina, polyvinylidene fluoride, and N-methylpyrrolidone, the mixture is milled and filtered to obtain a ceramic slurry. The ceramic slurry is coated on one side of a porous polyolefin-based membrane, and then dried and cooled to obtain a single-sided ceramic membrane. S2. Sodium alginate, conductive carbon black, 4A molecular sieve, and acrylic acid are mixed in water to obtain a composite slurry. The non-ceramic side of the single-sided ceramic separator is used as the coating surface, and the composite slurry is coated on the coating surface. Then, it is dried and cured at room temperature to obtain a sodium-ion battery composite separator.

[0029] In one embodiment, the mass ratio of nano-alumina, polyvinylidene fluoride, and N-methylpyrrolidone is (80~90):(5~15):(110~130); the drying temperature is 40~85℃; and the curing time at room temperature is 15~30h.

[0030] The present invention provides a sodium-ion battery, including a positive electrode, a negative electrode, and a sodium-ion battery composite separator as described above; the positive electrode is attached to the ceramic coating side of the sodium-ion battery composite separator, and the negative electrode is attached to the water-removing and dendrite-inhibiting coating side.

[0031] This invention does not impose any particular restrictions on the types of positive and negative electrode plates matched with the composite separator. Using the composite separator of this invention, long-term water removal, uniform control of sodium ion deposition, and cycle-resistant puncture prevention are all possible. Optionally, the composite separator is applicable to energy storage sodium-ion pouch cells and prismatic cells using Prussian blue-based, layered oxide-based, and polyanion positive electrodes paired with hard carbon negative electrodes. In one embodiment, the positive electrode is a sodium iron pyrophosphate electrode; the negative electrode is a hard carbon electrode; the sodium iron pyrophosphate electrode is mainly prepared from sodium iron pyrophosphate, conductive carbon black, and polyvinylidene fluoride in a mass ratio of (90~94):(4~6):(2~4), and the dry film thickness of the positive electrode is 90~110μm; the hard carbon electrode is mainly prepared from hard carbon, conductive carbon black, and sodium alginate in a mass ratio of (88~92):(5~7):(3~5), and the dry film thickness of the negative electrode is 100~120μm.

[0032] Specifically, in the following embodiments, the base membrane used is a porous polypropylene base membrane from Xingyuan Material brand. Sodium alginate is from Qingdao Mingyue Seaweed brand, and acrylic acid is from Sichuan Yindile brand. The conductive carbon black is Super P conductive carbon black. The 4A molecular sieve is a sodium-type molecular sieve.

[0033] Example 1 This embodiment provides a sodium-ion battery composite separator, which has a three-layer structure, as shown in the schematic diagram. Figure 1As shown, from top to bottom, it includes a ceramic coating 1, a porous polypropylene base film 2, and a water-removing and dendrite-inhibiting coating 3. The ceramic coating 1 is disposed on the side of the porous polypropylene base film 2 used for bonding the positive electrode of the sodium-ion battery, and the water-removing and dendrite-inhibiting coating 3 is disposed on the side of the porous polypropylene base film 2 used for bonding the negative electrode of the sodium-ion battery.

[0034] The porous polypropylene base membrane 2 has a thickness of 14 μm and a porosity of 45%. The ceramic coating 1 is a nano-alumina coating with a thickness of 1.2 μm; the average particle size of the nano-alumina is 300 nm. The dehydration and dendrite-inhibiting coating 3 has a thickness of 0.5 μm and includes a sodium alginate-bonded conductive matrix and 4A molecular sieves dispersed and fixed inside the sodium alginate-bonded conductive matrix. The average particle size of the 4A molecular sieve is 200 nm, and the pore size is 0.4 nm. By mass, the raw materials for preparing the dehydration and dendrite-inhibiting coating 3 include: 10 parts of 4A molecular sieve, 3 parts of sodium alginate, 1 part of acrylic acid, 86 parts of conductive carbon black, and 100 parts of deionized water.

[0035] The specific preparation steps of the above-mentioned sodium-ion battery composite separator are as follows: S1. Weigh out 85 parts by weight of nano-alumina, 10 parts by weight of polyvinylidene fluoride (PVDF), and 120 parts by weight of N-methylpyrrolidone (NMP). Add PVDF to NMP and stir at 50 r / min for 2 h at room temperature. Then add nano-alumina and mix well. Subsequently, mill the mixture in a sand mill for 1.5 h, filter it through a 200-mesh filter, and let it stand to defoam, thus obtaining a ceramic slurry.

[0036] The porous polypropylene base film is loaded onto an unwinding device, and the ceramic slurry obtained above is coated onto one side of the base film by a micro-gravure coating machine at a film speed of 20m / min. The thickness of the dry ceramic coating obtained after coating is controlled to be 1.2μm. Then it is sent into a low temperature gradient oven with a total length of 12m and dried in sections at 60℃, 75℃ and 85℃. After cooling and winding, a single-sided ceramic diaphragm is obtained.

[0037] S2. Weigh out 10 parts by weight of 4A molecular sieve, 3 parts by weight of sodium alginate, 1 part by weight of acrylic acid, 86 parts by weight of conductive carbon black, and 100 parts by weight of deionized water. First, add sodium alginate and acrylic acid to deionized water and stir at low speed for 3 hours at room temperature (20~30℃) and 200 r / min until completely swollen and dissolved. Then, add conductive carbon black and 4A molecular sieve in sequence and continue stirring at low speed for 40 minutes. Then, vacuum stir in a planetary mixer with a vacuum degree of -0.08MPa for 60 minutes at a stirring speed of 1200 r / min. Finally, filter through a 150-mesh filter to remove agglomerated particles to obtain a composite slurry.

[0038] The single-sided ceramic separator was again coated using a microgravure coating machine, with the non-ceramic side as the coating surface. The coating was applied at a film-carrying speed of 20 m / min, and the thickness of the dry coating was controlled to be 0.5 μm. After coating, the separator was placed in a low-temperature gradient oven and dried in stages at 40℃, 55℃, and 70℃ to prevent the high-temperature decomposition of sodium alginate. Finally, the double-sided coated separator was placed in a dust-free, low-humidity workshop (dew point ≤ -40℃) and aged at room temperature for 24 hours to release the internal stress of the coating. This yielded the sodium-ion battery composite separator of this embodiment.

[0039] This embodiment also provides a sodium-ion battery, which includes a positive electrode, a negative electrode, and the composite separator of this embodiment. The entire assembly and electrolyte injection process is completed in an argon-filled glove box production line with a water oxygen content of <0.1ppm. The specific steps are as follows: (1) Electrode preparation In the preparation of the positive electrode sheet, 92 wt% sodium iron pyrophosphate (NFPP), 5 wt% conductive carbon black, and 3 wt% PVDF were mixed, and NMP was added and stirred evenly to prepare a positive electrode slurry with a solid content of 60 wt%. The positive electrode slurry was coated onto the surface of a 14 μm thick aluminum foil current collector, then dried, rolled, and cut to obtain the positive electrode sheet. The dry film thickness of the coated positive electrode was 100 μm, and the areal density of the electrode sheet after rolling was 12 mg / cm³. 2 .

[0040] In the preparation of the negative electrode sheet, a negative electrode slurry was prepared by adding deionized water to 90 wt% hard carbon, 6 wt% conductive carbon black, and 4 wt% sodium alginate, with a solid content of 45 wt%. The negative electrode slurry was then coated onto the surface of an 8 μm thick copper foil current collector, followed by drying, rolling, and cutting to obtain the negative electrode sheet. The dry film thickness of the coated negative electrode was 110 μm, and the areal density of the electrode sheet after rolling was 10 mg / cm³. 2 The positive and negative electrodes are cut into standard sizes and aluminum tabs are welded on. Then they are placed in a vacuum oven at 80°C for 12 hours to completely remove the moisture adsorbed on the electrodes.

[0041] (2) Winding assembly Prepare the sodium-ion battery composite separator obtained in this embodiment, as well as the aforementioned positive and negative electrode sheets. During assembly, the ceramic coating side of the composite separator is attached to the positive electrode sheet, and the water-removing and dendrite-inhibiting coating side is attached to the negative electrode sheet. The positive electrode sheet, composite separator, and negative electrode sheet are alternately stacked and wound to form a battery core, with one side of the separator extending 1.5 mm beyond the edge of the electrode sheet to avoid direct contact between the positive and negative electrodes and causing a short circuit. Subsequently, the core is inserted into a molded aluminum-plastic film casing, and the three sides of the aluminum-plastic film are heat-sealed, leaving a single-sided liquid injection port for later use.

[0042] (3) Liquid injection and sealing The assembled battery cell from step (2) was placed in a vacuum oven at 85°C for 24 hours to remove moisture from the core. It was then transferred to an argon glove box, where a standard sodium-ion battery electrolyte containing 1 mol / L NaPF6 (a 1 / 1 volume ratio EC / DME mixed solvent) was injected into the cell. The injection volume was 1.8 times the total pore volume of the core. After injection, the cell was allowed to stand at room temperature for 12 hours to allow the electrolyte to fully wet the electrodes and separator. Vacuum evacuation was then performed to remove gas, and finally, the injection port was heat-sealed to complete the overall sealing of the battery cell.

[0043] (4) Composition and equilibrium settling After sealing the battery cell in step (3), remove it from the glove box and pre-charge it to 3.0V at a small current of 0.05C under a constant temperature environment of 25°C to complete the formation process. Let it stand for 24 hours to promote the formation of a stable SEI passivation film on the negative electrode surface. Then, use a 0.5C current charge-discharge cycle for 3 times to complete the capacity assessment and screen the qualified battery cells. The qualified battery cells are left to stand at room temperature for 72 hours to allow the moisture inside the battery cell to be fully adsorbed by the membrane molecular sieve and reach a moisture balance state, thus obtaining a soft-pack full-cell battery, which is the sodium-ion battery of this embodiment. Then, various electrochemical and safety performance tests are carried out.

[0044] Example 2 This embodiment provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1, except that: the porous polypropylene base membrane has a thickness of 12 μm and a porosity of 42%. The ceramic coating is a nano-alumina coating with a thickness of 1.8 μm; the average particle size of the nano-alumina is 200 nm. The thickness of the dehydration and dendrite-inhibiting coating is 0.4 μm. The average particle size of the 4A molecular sieve is 100 nm, and the pore size is 0.4 nm. By mass, the raw materials for preparing the dehydration and dendrite-inhibiting coating include: 8 parts of 4A molecular sieve, 3 parts of sodium alginate, 1 part of acrylic acid, 88 parts of conductive carbon black, and 100 parts of deionized water, with other parameters the same as in Example 1.

[0045] This embodiment also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of this embodiment for battery assembly, and the battery manufacturing process is the same as in Embodiment 1.

[0046] Example 3 This embodiment provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1, except that: the porous polypropylene base membrane has a thickness of 16 μm and a porosity of 47%. The ceramic coating is a nano-alumina coating with a thickness of 1.0 μm and an average particle size of 400 nm. The dehydration and dendrite-inhibiting coating has a thickness of 0.7 μm. The 4A molecular sieve has an average particle size of 300 nm and a pore size of 0.4 nm. By mass, the raw materials for preparing the dehydration and dendrite-inhibiting coating include: 14 parts of 4A molecular sieve, 5 parts of sodium alginate, 1 part of acrylic acid, 80 parts of conductive carbon black, and 100 parts of deionized water, with other parameters the same as in Example 1.

[0047] This embodiment also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of this embodiment for battery assembly, and the battery manufacturing process is the same as in Embodiment 1.

[0048] Example 4 This embodiment provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1, except that: the porous polypropylene base membrane has a thickness of 14 μm and a porosity of 45%. The ceramic coating is a nano-alumina coating with a thickness of 1.2 μm; the average particle size of the nano-alumina is 300 nm. The thickness of the dehydration and dendrite-inhibiting coating is 0.5 μm. The average particle size of the 4A molecular sieve is 200 nm, and the pore size is 0.4 nm. By mass, the raw materials for preparing the dehydration and dendrite-inhibiting coating include: 12 parts of 4A molecular sieve, 3 parts of sodium alginate, 1 part of acrylic acid, 84 parts of conductive carbon black, and 100 parts of deionized water, with other parameters the same as in Example 1.

[0049] This embodiment also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of this embodiment for battery assembly, and the battery manufacturing process is the same as in Embodiment 1.

[0050] Example 5 This embodiment provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1, except that: the porous polypropylene base membrane has a thickness of 14 μm and a porosity of 40%. The ceramic coating is a nano-alumina coating with a thickness of 1.5 μm; the average particle size of the nano-alumina is 300 nm. The thickness of the dehydration and dendrite-inhibiting coating is 0.6 μm. The average particle size of the 4A molecular sieve is 200 nm, and the pore size is 0.4 nm. By mass, the raw materials for preparing the dehydration and dendrite-inhibiting coating include: 9 parts of 4A molecular sieve, 4 parts of sodium alginate, 1 part of acrylic acid, 86 parts of conductive carbon black, and 100 parts of deionized water, with other parameters the same as in Example 1.

[0051] This embodiment also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of this embodiment for battery assembly, and the battery manufacturing process is the same as in Embodiment 1.

[0052] Example 6 This embodiment provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1, except that: the porous polypropylene base membrane has a thickness of 14 μm and a porosity of 48%. The ceramic coating is a nano-alumina coating with a thickness of 1.5 μm; the average particle size of the nano-alumina is 300 nm. The thickness of the dehydration and dendrite-inhibiting coating is 0.8 μm. The average particle size of the 4A molecular sieve is 200 nm, and the pore size is 0.4 nm. By mass, the raw materials for preparing the dehydration and dendrite-inhibiting coating include: 15 parts of 4A molecular sieve, 4 parts of sodium alginate, 1 part of acrylic acid, 80 parts of conductive carbon black, and 100 parts of deionized water, with other parameters the same as in Example 1.

[0053] This embodiment also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of this embodiment for battery assembly, and the battery manufacturing process is the same as in Embodiment 1.

[0054] Comparative Example 1 This comparative example provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1. The difference is that the dehydration and dendrite-inhibiting coating is omitted, while the other parameters are the same as those in Example 1.

[0055] The comparative example also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of the comparative example for battery assembly, and the battery manufacturing process is the same as in Example 1.

[0056] Comparative Example 2 This comparative example provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1. The difference is that the 4A molecular sieve in the dehydration dendrite-inhibiting coating is omitted. That is, the raw materials for the preparation of the dehydration dendrite-inhibiting coating include: 3 parts sodium alginate, 1 part acrylic acid, 96 parts conductive carbon black, and 100 parts deionized water. The other parameters are the same as those in Example 1.

[0057] The comparative example also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of the comparative example for battery assembly, and the battery manufacturing process is the same as in Example 1.

[0058] Comparative Example 3 This comparative example provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1. The difference is that sodium alginate and acrylic acid are omitted from the deionized dendrite-inhibiting coating. That is, the raw materials for preparing the deionized dendrite-inhibiting coating include: 10 parts of 4A molecular sieve, 90 parts of conductive carbon black, and 100 parts of deionized water. The other parameters are the same as those in Example 1.

[0059] The comparative example also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of the comparative example for battery assembly, and the battery manufacturing process is the same as in Example 1.

[0060] Comparative Example 4 This comparative example provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1. The difference lies in the omission of the dehydration and dendrite-inhibiting coating, and the addition of 4A molecular sieve to the ceramic coating. Specifically, the ceramic slurry preparation process is as follows: 85 parts by mass of nano-alumina, 10 parts by mass of polyvinylidene fluoride (PVDF), 120 parts by mass of N-methylpyrrolidone (NMP), and 10 parts by mass of 4A molecular sieve are weighed. PVDF is added to NMP and stirred at 50 r / min for 2 h at room temperature. Then, nano-alumina and 4A molecular sieve are added and mixed evenly. Subsequently, the mixture is milled for 1.5 h using a sand mill, filtered through a 200-mesh filter, and allowed to stand to defoam, yielding the ceramic slurry. The remaining parameters are the same as in Example 1.

[0061] The comparative example also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of the comparative example for battery assembly, and the battery manufacturing process is the same as in Example 1.

[0062] Comparative Example 5 This comparative example provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1. The difference is that 5A molecular sieve of equal mass is used instead of 4A molecular sieve, and the other parameters are the same as those in Example 1.

[0063] The comparative example also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of the comparative example for battery assembly, and the specific process is the same as in Example 1.

[0064] Comparative Example 6 This comparative example provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1. The difference is that the thickness of the dehydration and dendrite-inhibiting coating is set to be the same as that of the ceramic coating, which is 1.2 μm. The other parameters are the same as those in Example 1.

[0065] The comparative example also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of the comparative example for battery assembly, and the battery manufacturing process is the same as in Example 1.

[0066] Comparative Example 7 This comparative example provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1. The difference between the two is that the amount of 4A molecular sieve in the dehydration and dendrite-inhibiting coating is increased. That is, the raw materials for preparing the dehydration and dendrite-inhibiting coating include: 20 parts of 4A molecular sieve, 3 parts of sodium alginate, 1 part of acrylic acid, 76 parts of conductive carbon black, and 100 parts of deionized water.

[0067] The comparative example also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of the comparative example for battery assembly, and the battery manufacturing process is the same as in Example 1.

[0068] Comparative Example 8 This comparative example provides a sodium-ion battery composite separator, whose composition and preparation method are basically the same as those in Example 1. The difference is that the thickness of the ceramic coating is set to be the same as that of the water-removing and dendrite-inhibiting coating, which is 0.5 μm. The other parameters are the same as those in Example 1.

[0069] The comparative example also provides a sodium-ion battery, which uses the sodium-ion battery composite separator of the comparative example for battery assembly, and the battery manufacturing process is the same as in Example 1.

[0070] Test Example 1: Diaphragm Puncture Strength and Wetting Angle Test The present invention examines the safety performance and electrolyte wetting effect of the composite diaphragms obtained in Examples 1-6 and Comparative Examples 1-8 by testing their puncture strength and wetting angle.

[0071] The test method for diaphragm puncture strength is as follows: According to GB / T 37841-2019 "Test Method for Puncture Resistance of Plastic Films and Sheets", a film puncture strength tester is used. A 100mm×100mm diaphragm sample is cut and fixed in a circular clamp. A standard puncture needle with a diameter of 1mm is selected, and the puncture pressure speed is 50mm / min. The maximum force at the moment the diaphragm is punctured is recorded, with the unit being grams of force (gf). Ten samples are tested in each group, and the arithmetic mean is taken.

[0072] The electrolyte wetting angle was tested using a contact angle meter (seat drop method) at a room temperature of 25℃ and a humidity of 30%. A flattened separator sample was fixed on the stage. A standard sodium-ion battery electrolyte (1 mol / L NaPF6, solvent being a 1 / 1 volume ratio EC / DME mixture) was used. A 3 μL drop of electrolyte was dropped onto the separator coating surface using a microsyringe. After the droplet stabilized for 2 seconds, an image was captured. The software automatically calculated the electrolyte wetting angle against the separator surface. Five different points were tested for each sample, and the average value was taken.

[0073] The test results of puncture strength and wetting angle of the sodium-ion battery composite separators prepared in Examples 1-6 and Comparative Examples 1-8 are shown in Table 1.

[0074] Table 1. Puncture strength and wetting angle of composite diaphragms

[0075] As shown in Table 1, the puncture strength of the composite membranes prepared in Examples 1-6 of this invention is in the range of 396-445 gf, all meeting the mechanical strength requirements of sodium electrolyte membranes. Simultaneously, the wetting angle of all composite membranes in these examples is <11°, exhibiting super-electrolyte affinity, far superior to ordinary polyolefin membranes (typically >40°). Comparison revealed that Comparative Example 3 (without sodium alginate and acrylic acid) had a wetting angle of 15.8°, demonstrating that sodium alginate and acrylic acid directly contribute to electrolyte wettability. Comparative Example 4 (with molecular sieve mixed into the ceramic layer) had a puncture strength of 425 gf and a wetting angle of 14.9°, indicating that the molecular sieve placed on the positive electrode side in the ceramic layer cannot effectively capture moisture on the negative electrode side. Comparative Example 8, with a ceramic coating of only 0.5 μm, had a puncture strength of only 315 gf, severely insufficient, proving that the ceramic layer thickness needs to be ≥1.0 μm to ensure mechanical strength. In Comparative Example 6, when the thickness of the dehydration and dendrite-inhibiting coating was 1.2 μm, the wetting angle increased to 13.5°, indicating that the excessive coating thickness increased the resistance to the electrolyte transport path. In Comparative Example 7, when the molecular sieve was in excess, the wetting angle increased to 12.8°, indicating that the excessive molecular sieve caused agglomeration inside the coating and deterioration of the pore structure.

[0076] Test Example 2: Cell Moisture Balance and Battery Cycle Performance Test This invention examines the cell balance moisture content and battery cycle performance of sodium-ion batteries prepared with composite separators in Examples 1-6 and Comparative Examples 1-8, to investigate the battery cycle stability and cell application effect.

[0077] The test method for cell equilibrium moisture content is as follows: Based on GB / T 6283-2008 "Determination of Moisture Content in Chemical Products - Karl Fischer Method". The cells of a soft-pack sodium-ion battery, after the separator has been assembled, the electrolyte filled and sealed, and allowed to stand for 72 hours to reach moisture equilibrium, are disassembled in a glove box (water and oxygen content < 0.1 ppm). The internal electrolyte is extracted, and the total moisture content of the electrolyte is measured using a coulometric Karl Fischer moisture analyzer. The unit of measurement is ppm (mg / kg). Three parallel groups of cells are tested, and the average value is taken.

[0078] The test method for capacity retention after 500 cycles is as follows: According to the general requirements for sodium-ion batteries, the sodium-ion batteries prepared in Examples 1-6 and Comparative Examples 1-8 were charged at a constant temperature of 25°C with a constant current and constant voltage of 0.5C to a cutoff voltage of 3.6V, allowed to stand for 10 minutes, and then discharged at a constant current of 0.5C to a cutoff voltage of 1.5V. This constitutes one complete charge-discharge cycle. After 500 consecutive cycles, the discharge capacity on the 500th cycle was divided by the initial discharge capacity on the first cycle to obtain the capacity retention after 500 cycles.

[0079] The cell equilibrium moisture content and battery cycle performance of the sodium-ion battery composite separators prepared in Examples 1-6 and Comparative Examples 1-8 are shown in Table 2.

[0080] Table 2. Cell Balance Moisture and Battery Cycle Performance

[0081] As shown in Table 2, the cells of Comparative Example 1 (126 ppm) and Comparative Example 2 (118 ppm) of this invention have extremely high moisture content, indicating that the molecular sieve is the core functional component for water removal, and the coating's water removal ability is poor without the molecular sieve. Meanwhile, the moisture content of Examples 1-6 of this invention is ≤19 ppm, far lower than that of Comparative Examples 1 and 2, proving that the 4A molecular sieve can effectively adsorb water molecules in the electrolyte, controlling the moisture content at an extremely low level. Furthermore, the capacity retention rate after cycling is related to the moisture content of the cell. Higher moisture content leads to the hydrolysis of NaPF6 to generate HF, which corrodes the positive electrode active material (NFPP) and damages the negative electrode SEI film, resulting in irreversible capacity loss. This invention reduces the moisture content from 126 ppm to ≤19 ppm, improving the capacity retention rate after cycling by 15-17 percentage points, effectively improving the electrochemical stability of the battery.

[0082] In summary, the composite separator provided by this invention has a three-layer structure consisting of a ceramic coating (positive electrode side), a porous base membrane, and a water-removing and dendrite-inhibiting coating (negative electrode side). The ceramic coating provides thermal stability and mechanical support (puncture strength ≥396gf), while the water-removing coating enables precise adsorption of moisture (equilibrium moisture ≤19ppm). This achieves synergistic optimization of puncture strength, electrolyte wettability, moisture control, and cycle stability, making it suitable for use in energy storage sodium-ion batteries.

[0083] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art can make various improvements and modifications without departing from the spirit and principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A sodium-ion battery composite separator, characterized in that, The sodium-ion battery composite separator has a three-layer composite structure, comprising a ceramic coating, a porous polyolefin base membrane, and a water-removing and dendrite-inhibiting coating. The ceramic coating is disposed on the side of the porous polyolefin base membrane used for bonding the positive electrode of the sodium-ion battery; the water-removing and dendrite-inhibiting coating is disposed on the side of the porous polyolefin base membrane used for bonding the negative electrode of the sodium-ion battery. The thickness of the ceramic coating is greater than the thickness of the water-removing and dendrite-inhibiting coating. The raw materials for preparing the water-removing and dendrite-inhibiting coating, by mass parts, include: 8-15 parts of 4A molecular sieve, 3-5 parts of sodium alginate, 0.5-2 parts of acrylic acid, and 80-88 parts of conductive carbon black.

2. The sodium-ion battery composite separator according to claim 1, characterized in that, The porous polyolefin-based membrane has a thickness of 12~16μm and a porosity of 40%~48%; the porous polyolefin-based membrane is made of polypropylene or polyethylene.

3. The sodium-ion battery composite separator according to claim 1, characterized in that, The thickness of the ceramic coating is 1~2μm; the ceramic coating is a nano-alumina coating, and the average particle size of the nano-alumina is 200~400nm.

4. The sodium-ion battery composite separator according to claim 1, characterized in that, The thickness of the dehydration and dendrite-inhibiting coating is 0.4~0.8μm.

5. The sodium-ion battery composite separator according to claim 1, characterized in that, The 4A molecular sieve has a particle size of 100~300nm and a pore size of 0.3~0.5nm.

6. The sodium-ion battery composite separator according to claim 1, characterized in that, The raw materials for preparing the water-removing and dendrite-inhibiting coating also include 80-120 parts of water.

7. A method for preparing a sodium-ion battery composite separator as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. After mixing nano-alumina, polyvinylidene fluoride, and N-methylpyrrolidone, the mixture is milled and filtered to obtain a ceramic slurry. The ceramic slurry is coated on one side of a porous polyolefin-based membrane, and then dried and cooled to obtain a single-sided ceramic membrane. S2. Sodium alginate, conductive carbon black, 4A molecular sieve, and acrylic acid are mixed in water to obtain a composite slurry. The non-ceramic side of the single-sided ceramic separator is used as the coating surface, and the composite slurry is coated on the coating surface. Then, it is dried and aged at room temperature to obtain the sodium-ion battery composite separator.

8. The method for preparing the sodium-ion battery composite separator according to claim 7, characterized in that, The mass ratio of nano-alumina, polyvinylidene fluoride, and N-methylpyrrolidone is (80~90):(5~15):(110~130); the drying temperature is 40~85℃; and the room temperature curing time is 15~30h.

9. A sodium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, and a sodium-ion battery composite separator as described in any one of claims 1 to 6; the positive electrode is attached to the ceramic coating side of the sodium-ion battery composite separator, and the negative electrode is attached to the water-removing and dendrite-inhibiting coating side.

10. The sodium-ion battery according to claim 9, characterized in that, The positive electrode is a sodium iron pyrophosphate electrode; the negative electrode is a hard carbon electrode; the sodium iron pyrophosphate electrode is mainly prepared from sodium iron pyrophosphate, conductive carbon black, and polyvinylidene fluoride in a mass ratio of (90~94):(4~6):(2~4), and the dry film thickness of the positive electrode is 90~110μm; the hard carbon electrode is mainly prepared from hard carbon, conductive carbon black, and sodium alginate in a mass ratio of (88~92):(5~7):(3~5), and the dry film thickness of the negative electrode is 100~120μm.